2011
DOI: 10.1111/j.1439-0531.2011.01890.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Length of Progestagen Treatment and the Time of Oestradiol Benzoate Application on the Ovulatory Follicle Size and Ovulation Time in Anoestrous and Cyclic Beef Cows

Abstract: Previous research from our laboratory in beef cattle suggests that the pre-ovulatory follicle size, maturity and subsequent susceptibility to gonadotropin are influenced by the length of progestagen treatment in artificial insemination programme in beef cows. To test this hypothesis, two experiments were conducted. In experiment 1, 35 anoestrous beef cows received an intravaginal sponge containing 200 mg of medroxyprogesterone acetate. The treatment lasted for 7 (n = 12), 8 (n = 11) or 9 (n = 12) days. Half of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Estradiol usage in cattle is still legal in most countries around the world and it is being used extensively for oestrus synchronization programs (Butler et al 2012, Manes et al 2012 while its application is not allowed in food producing animals in the European Union.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol usage in cattle is still legal in most countries around the world and it is being used extensively for oestrus synchronization programs (Butler et al 2012, Manes et al 2012 while its application is not allowed in food producing animals in the European Union.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant follicle (DF) of a wave was defined as that one that reached the largest diameter (Ginther, Kastelic, & Knopf, ). The time of ovulation was defined as the average time between the last observation of the dominant follicle and the time at which the dominant follicle disappeared (ovulation), which also determined the ovulatory follicle diameter (Manes, Aller, Callejas, Hozbor, & Alberio, ; Uslenghi et al., ). On day 22 (approximately 12 days after ovulation), another ultrasound evaluation was performed to confirm ovulation by the presence of a CL (Carvalho et al., ); the CL area was measured with the ultrasound equipment's caliper system.…”
Section: Methodsmentioning
confidence: 99%
“…Other evidence has confirmed EB treatment efficiency for the induction of ovulation in buffalo. Studies have shown that EB treatment induces considerable release of LH (JACOMINI et al, 2014), has a low cost (BARROS et al, 2000;MANES et al, 2012) and maintains high circulating oestradiol concentrations, which likely creates a better uterine environment for embryonic development (BRIDGES et al, 2012).…”
Section: Discussionmentioning
confidence: 99%